Comparison of long-stemmed cementless hemiarthroplasty with proximal femur nail in unstable intertrochanteric femur fractures over 85 years of age - Mirza Zafer Dağtaş (Journal of Surgery and Medicine, 2020)
Aim: The most appropriate treatment option for intertrochanteric femoral fractures is still controversial. While there are articles showing that proximal femoral nails are superior to partial prostheses, other studies claim that partial prostheses result in better patient outcomes. We aimed to compare long-stemmed cementless hemiarthroplasty (LFS-BPH) and proximal femur nail (PFN), which are the treatment options applied in unstable intertrochanteric hip fractures in patients over 85 years of age. Methods: The records of 64 patients with unstable intertrochanteric femur fractures who were operated between May 2016 and December 2018 in the Orthopedics and Traumatology Clinic of Maltepe University Medical Faculty Hospital were evaluated. A retrospective cohort study was conducted and 42 patients who met the inclusion criteria were included in the study. The patients were divided into 2 groups as the proximal nail group and the prosthesis group, and evaluated in terms of total hospitalization time, operation time, amount of blood transfusion, time until the patient walked independently, postoperative complications, and Harris hip scores. Results: There were statistically significant differences in favor of the PP group in terms of total length of stay, fully independent mobilization time, deep vein thrombosis and decubitus development in the postoperative period. There was no difference between LFS-BPH and PFN in terms of total hospitalization time, blood transfusion amount, and Harris hip scores in unstable intertrochanteric hip fractures occurring above 85 years of age. Conclusion: LFS-BPH was superior to PFN in terms of operation time, early independent mobilization, reduction of deep vein thrombosis and decubitus development rate in the postoperative period.